Cross‐sectional and longitudinal association between atrial fibrillation and sarcopenia: Findings from the Korean frailty and aging cohort study - Ga Yang Shim; Miji Kim; Chang Won Won (Wiley, 2024)
Abstract Background Sarcopenia is commonly observed in patients with cardiovascular diseases. However, studies on the association between sarcopenia and atrial fibrillation and their causal relationships are limited. We performed cross‐sectional and longitudinal analyses to investigate the association between sarcopenia and atrial fibrillation among community‐dwelling older adults. Methods A total of 2225 participants from the Korean Frailty and Aging Cohort Study (KFACS) from 2016 to 2017 were included in this cross‐sectional analysis. Sarcopenia was defined according to the Asian Working Group for Sarcopenia 2019 consensus. Atrial fibrillation was diagnosed on the basis of electrocardiographic findings. We investigated whether atrial fibrillation increased the risk of incident sarcopenia 2 years later and whether sarcopenia, in turn, increased the 2‐year risk of developing atrial fibrillation using KFACS data from 2018 to 2019. Results Of the 2225 participants (54.2% women; mean age 76.0 ± 3.9 years), 509 (22.9%) had sarcopenia at baseline. In the cross‐sectional analysis, sarcopenia was associated with atrial fibrillation after multivariate adjustment [odd ratio (OR), 2.127; 95% confidence interval (CI), 1.240-3.648; P = 0.006]. Among the sarcopenia components, low physical performance was associated with atrial fibrillation (OR, 1.872; 95% CI, 1.123-3.120; P = 0.016). During the 2‐year follow‐up period, atrial fibrillation was not associated with new‐onset of sarcopenia (OR, 1.483; 95% CI, 0.597-3.685; P = 0.396), and sarcopenia also did not significantly increase the risk of incident atrial fibrillation (OR, 1.120; 95% CI, 0.384-3.264; P = 0.836). Conclusions Although we found a significant association between sarcopenia and atrial fibrillation in a cross‐sectional analysis, we could not establish a causal relationship between the two based on 2 years of follow‐up. Further research with long‐term follow‐up is required to identify causal relationship between atrial fibrillation and sarcopenia.